Rockets and crackers - Westcott, Alvin M.; Le Blanc, Lee (Mankato, Minnesota : Oddo Publishing, 1970)
A brother and sister discover and capture a band of smugglers ensconced in a secret island cove.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Smuggling -- Fiction